Risk factors for gallbladder cancer - Suchodolska, Magdalena; Świerczyńska, Blanka; Undziakiewicz, Adrian; Smoluchowski, Krzysztof; Sekuła, Michał (Journal of Education, Health and Sport, 2020)
Introduction and purpose: Gallbladder cancer is the most common neoplasm of the bile duct. Early GBC is usually asymptomatic, but is prone to early metastases. This means that most GBC cases are diagnosed very late, and this contributes to the poor prognosis of this disease. Less than 20% of GBC cases qualify for a potentially curable surgical resection at the moment of diagnosis. The article is an overview of available literature describing current epidemiology and etiological risk factors associated with the development of gallbladder cancer (GBC). We performed a review of the articles on the etiology and GBC carcinomatosis. Brief description of the state of knowledge: We divided risk factors of GBC into independent and dependent. The independent risk factors are: age, sex, cholelithiasis, porcelain gallbladder, gallbladder polyp, anomalous junction of the pancreaticobiliary ductal system, high BMI and obesity, and Helicobacter pylori. On the other hand, the dependent risk factors are: age of first pregnancy and number of pregnancies, xanthogranulomatous cholecystitis, lipid peroxidation products, and aflatoxins. Gallbladder cancer appears to be a multifactorial disease, but the main risk factors are: cholelithiasis and porcelain gallbladder developing from chronic cholecystitis. Conclusions: For understanding the etiopathology of GBC more studies have to be conducted, what may allow to establish reliable biomarkers and invent new preventive strategies and more effective treatment.